White Terror : The Horror Film from Obama to Trump - Meeuf, Russell, 1981- (Book collections on Project MUSE., 2022)
"What kinds of terror lurk beneath the surface of White respectability? Many of the top-grossing US horror films between 2008 and 2016 relied heavily on themes of White, patriarchal fear and fragility: outsiders disrupting the sanctity of the almost always White family, evil forces or transgressive ideas transforming loved ones, and children dying when White women eschew traditional maternal roles. Horror film has a long history of radical, political commentary, and Russell Meeuf reveals how racial resentments represented specifically in horror films produced during the Obama era gave rise to the Trump presidency and the Make America Great Again movement. Featuring films such as The Conjuring and Don't Breathe, White Terror explores how motifs of home invasion, exorcism, possession, and hauntings mirror cultural debates around White masculinity, class, religion, socioeconomics, and more. In the vein of Jordan Peele, White Terror exposes how White mainstream fear affects the horror film industry, which in turn cashes in on that fear and draws voters to candidates like Trump"--